Celebrating Acadian milestones in 2004. Issue 2 (September 2018) - Keppie, Christina
Abstract : In the year when Canadians celebrate 150 years of confederation, we recognise the frequent absence of cultural minorities from national commemorative events, such as the Acadians. However, minority commemorative events serve as a strong factor in helping maintain ideologies, as imposed on the minority's general population by their cultural elite. In addition to a synthesis of ideological evidence in Acadian commemorative events, the current project addresses the importance of ethnographic work in the study of ideology of small 'nations'. Drawing upon a series of open-ended interviews, a collection known as the 2004 ArtcaDIT corpus collected by Le Musée acadien du Québec, this article details the results of a short content analysis of transcribed oral testimonies by New Brunswick Acadians who reflect on the impact and purpose of the 2004 Acadian Quadricentennial Celebration. While the data set is small, patterns suggest that views among New Brunswick Acadians of 2004 do in fact corroborate the Acadian national ideology imposed by the Acadian elite who have sought cultural minority protection of l'Acadie moderne through linguistic rights and duality. However, these results are not exclusive, as a number of testimonies also suggest a lingering adherence to traditional Acadian views that emphasises the importance of history and genealogy. Finally, this article demonstrates again the presence of the Acadian 'dilemma' which could be alleviated by further studying ideologies within other Acadian regions.